2023
DOI: 10.1021/acscatal.3c00655
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the Surface and Bulk Reactivities of MXenes and Catalytic Activity Tuning through Surface Chemistry Modification

Abstract: MXenes, a family of two-dimensional (2D) materials based on transition metal carbides and nitrides, show great promise as electrocatalysts for electrochemical reactions but suffer from a lack of fundamental understanding of their electrocatalytic mechanisms. Decoupling the surface and bulk reactivities are key to understanding the electrocatalytic mechanisms of these emerging nanomaterials. Herein, we use Raman spectroscopy to decouple the surface and bulk reactivities of the Ti 2 NT x MXene. By attenuating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 71 publications
5
22
1
Order By: Relevance
“…The A 1g vibrations located in the low-frequency region at around 280 cm –1 are labeled symmetric and represent the out-of-plane vibration of transition metal atoms. Previous reports have discussed some discrepancies in the assignment of E g and A 1g vibrations for other M 2 X structures in the 100–300 cm –1 region; however, according to the theoretical calculations and polarized Raman spectroscopy results, the lower-frequency peak in that region corresponds to in-plane vibration, followed by the out-of-plane vibration peak. Additionally, it has been shown computationally that the surface terminations weaken the motion of M and X atoms, , redshifting those low-frequency region peaks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The A 1g vibrations located in the low-frequency region at around 280 cm –1 are labeled symmetric and represent the out-of-plane vibration of transition metal atoms. Previous reports have discussed some discrepancies in the assignment of E g and A 1g vibrations for other M 2 X structures in the 100–300 cm –1 region; however, according to the theoretical calculations and polarized Raman spectroscopy results, the lower-frequency peak in that region corresponds to in-plane vibration, followed by the out-of-plane vibration peak. Additionally, it has been shown computationally that the surface terminations weaken the motion of M and X atoms, , redshifting those low-frequency region peaks.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of laser has been shown to vary the spectra of MXenes based on the resonance effect and penetration depth. , Since the laser choice can affect the spectra, the spectra collected with 633 and 785 nm lasers (the only two other wavelengths available in our instrument) for analyzed MXenes are reported in Figure S5. The peak intensities and the background change for all of the MXenes, making certain peaks seem to appear/disappear; however, the Raman shift of the peaks remains independent of excitation wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…These techniques not only shed light on the structural aspects and composition of MXenes, but also allow us to establish correlations with their properties. By exploring the structure-property relations, we aim to elucidate the mechanisms that govern MXenes' performance, enabling the design and In situ HF-formation etching [99] Alkali etching [88] Electrochemical etching [89] Organic polar solvent etching [37] Halogen etching [71] Ta 2 C Molten salt etching [32] Ti 2 C HF etching [100] In situ HF-formation etching [101] Cr 2 C Electrochemical HCl etching [102] V 2 C HF etching [103] In situ HF-formation etching [104] V 4 C 3 HF etching [105] Ta 4 C 3 HF etching [33] Mo 2 C HF etching [106] In situ HF-formation etching [107] HCl etching [39] CVD [108] Salt-templated growth [94] 𝛼-Mo 2 C CVD [109] Zr 3 C 2 HF etching [110] Hf 3 C 2 HF etching [111] ScC x Alkali etching [112] YC x HF etching [113] In situ HF-formation etching Nb 4 C 3 HF etching [114] Nb 2 C HF etching [115] Ti 3 (C 0.5 N 0.5 ) 2 Molten salt etching [32] HF etching [100] Ti 3 C 2-y O y In situ HF-formation etching [79] Ti 2 N In situ HF-formation etching [116] Molten salt etching [117] Ti 4 N 3 Molten salt etching [118] V 2 N HF etching [119] Mo 2 N Ammoniated [120] W 2 N Salt-templated growth [121] Mn 3 N 2 Salt-templated growth [93] (V 0.5 Cr 0.5 ) 3 C 2 HF etching [100] (Ti 0.5 V 0.5 ) 3 C 2 In situ HF-formation et...…”
Section: Structure-property Relations In Mxenesmentioning
confidence: 99%
“…Ti 2 NT x MXene was also shown to have faster reaction kinetics compared to both the counterpart Ti 3 C 2 T x MXene and benchmark Pt/C. A work by Yoo and Djire reports the Ti 2 NT x MXene to have a high HER electrocatalytic activity under 0.5 M KOH, achieved through modifications of the overall synthesis process . In regards to applications as sensing materials, Zhang et al suggested that 2D Ti 2 NT 2 monolayer can work as efficient nitrogen-containing gas (NCGs) sensing materials because of its nice reversibility from reducing NCG adsorption energies and sufficient charge transfer of Ti 2 NT 2 to the termination group of the sensing material .…”
Section: Introductionmentioning
confidence: 99%